Predictors of asylum seekers' mental health course in the early stages of resettlement: results of a longitudinal study - Kindermann, David; Zeyher, Valentina; Nagy, Ede; Brandenburg-Ceynowa, Hannah; Friederich, Hans-Christoph; Bozorgmehr, Kayvan; Nikendei, Christoph (Journal of psychosomatic research, 2020)
Objective - Asylum seekers who have experienced persecution, war and torture show high prevalence rates of stress-related mental disorders. After arrival in the host country, the early stages of resettlement seem to be a particularly vulnerable phase characterized by social instability. This longitudinal study aimed to explore predictors of the asylum seekers' course of mental health during the transition phase from a state registration and reception center to municipal shelters. - Methods - We used hierarchical regression analysis to assess the symptom course of posttraumatic stress disorder (PTSD), depression, anxiety and panic disorders as well as well-being in n = 84 asylum seekers. The follow-up assessment took place three to five months after baseline assessment. The following blocks of possible predictors were included in the statistical models: (1) sociodemographic variables, (2) cultural background related variables, (3) psychometric measures of emotion regulation and sense of coherence and (4) time range to follow-up. - Results - Language proficiency, origin, religion and gender were stronger predictors of the asylum seekers' mental health course in the early stages of resettlement than emotion regulation and sense of coherence. - Conclusions - Sociodemographic and cultural background related variables, like language proficiency have a high psychosocial relevance for asylum seekers in the early phase of the asylum process. Therefore, language courses should be implemented progressively. Psychotherapy for asylum seekers should always be performed with awareness for cultural specific perspectives and acculturative adjustment processes.
Gesehen am 28.04.2020